1998
DOI: 10.1111/j.1349-7006.1998.tb00470.x
|View full text |Cite
|
Sign up to set email alerts
|

A Large Germline Deletion of the MEN1 Gene in a Family with Multiple Endocrine Neoplasia Type 1

Abstract: Multiple endocrine neoplasia type 1 (MEN1) is a familial cancer syndrome inherited as an autosomal dominant trait. Various heterozygous germline mutations of the responsible gene, MEN1, have been identified within its exons in many, but not all, affected individuals. We here demonstrate, by DNA polymorphism analysis and gene dosage analysis with polymerase chain reaction (PCR), a large heterozygous germline MEN1 deletion in a kindred with MEN1, in whom no mutation could be detected in the PCR-amplified exons. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(35 citation statements)
references
References 18 publications
3
32
0
Order By: Relevance
“…Microsatellite length polymorphism around the MEN1 locus was analyzed using polymorphic DNA markers on chromosome 11q13, PYGM and D11S4940, as described previously (19). PYGM and D11S4940 are located centromeric and telomeric, respectively, to the MEN1 gene.…”
Section: Loh Studymentioning
confidence: 99%
“…Microsatellite length polymorphism around the MEN1 locus was analyzed using polymorphic DNA markers on chromosome 11q13, PYGM and D11S4940, as described previously (19). PYGM and D11S4940 are located centromeric and telomeric, respectively, to the MEN1 gene.…”
Section: Loh Studymentioning
confidence: 99%
“…However, it is to be noted that no mutations were found in some families with MEN 1 (Shimizu et al 1997;Bassett et al 1998). Some of these families may have a large deletion in the MEN1 gene (Kishi et al 1998), but a family with the clinical features of MEN 1 but not linked to Agarwal et al 1997;Shimizu et al 1997 d Bassett et al 1998 the MEN1 locus has also been reported (Stock et al 1997). Thus, absence of the MEN1 gene mutation, as determined by PCR and the following sequencing, cannot completely rule out the possibility that MEN 1 is present.…”
Section: Discussionmentioning
confidence: 98%
“…This may stem from a mutation in the untranslated region, an intron or the promoter region of the gene, or a large germline deletion which resulted in amplification of only the normal copy of MEN1 by PCR. Indeed, a large germline deletion of the MEN1 gene is reported in a Japanese kindred (Kishi et al 1998). Our case 3 showed typical MEN1 phenotypes and the inheritance of the disease was verified at least in two generations (his brother and a nephew), although the heterogeneity of enteropancreatic tumors within the family exists (carcinoid tumor, gastrinoma, and insulinoma).…”
Section: Discussionmentioning
confidence: 99%